The keys to coping with (extreme) space weather events.
With over 1,300 satellites in orbit and the millions of euros of investment they represent, better understanding and forecasting of the threats posed by space weather is required. The SPACESTORM project took up this challenge almost four years ago, and is now providing stakeholders with unique insights not only into future and past space weather, but also into, how engineers should adapt their designs to avoid service disruptions.